2018
DOI: 10.1177/0272684x18811016
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Early Sexual Debut Among Sexually Active Youth in Ghana

Abstract: Using the 2014 Ghana Demographic and Health Survey, this study explores the correlates of early sexual debut among 2,746 (males = 670 and females = 2,076) sexually active youth aged 15 to 24 years in Ghana. The results indicate that males aged 15 to 19 years (odds ratio [ OR] = 8.84, p < .001) and who had basic education ( OR = 3.17, p < .001) were significantly more likely to initiate sexual debut early. Urban males who had used modern contraceptive ( OR = 0.35, p < .001) were significantly less like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
43
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 27 publications
15
43
3
Order By: Relevance
“…Early sexual debut is common in African settings, with rates ranging from 26.8% in Nigeria to 55 percent in Ghana [ 15 , 16 ]. In this current study, the national prevalence of nonmarital early sexual initiation this current study recorded was 56.9% and in terms of regional prevalence, the highest (66.6%) prevalence was recorded in the Northern Region (now Northern, Savanna, and Northeast regions) and the lowest (39.7%) prevalence was recorded in the Greater Accra Region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early sexual debut is common in African settings, with rates ranging from 26.8% in Nigeria to 55 percent in Ghana [ 15 , 16 ]. In this current study, the national prevalence of nonmarital early sexual initiation this current study recorded was 56.9% and in terms of regional prevalence, the highest (66.6%) prevalence was recorded in the Northern Region (now Northern, Savanna, and Northeast regions) and the lowest (39.7%) prevalence was recorded in the Greater Accra Region.…”
Section: Discussionmentioning
confidence: 99%
“…Early sexual debut is common in African settings, with rates ranging from 26.8% in Nigeria to 55 percent in Ghana [ 15 , 16 ]. For adolescents to remain sexually abstinent, a dynamic interplay of variables such as sociocultural, faith, parent, and child connectedness plays a major role in the timing of sexual initiation [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have suggested exposure to media as an important factor in predicting adolescents' and young people's sexual and reproductive behaviour (Asante et al, 2018;Barber and Axinn, 2004;Cheng, 2011;Gupta et al, 2003;Wado et al, 2019). Growing evidence has revealed that young people need accurate information concerning their reproductive behaviour (Barber and Axinn, 2004;Cheng, 2011;Gupta et al, 2003).…”
Section: Study Findings In Relation To Other Studiesmentioning
confidence: 99%
“…It is however not known how the age of sexual debut in males influences their partnering patterns but it could partly be because of the fact that it influences the satisfaction derived from the intimate relationships Harden, Quinn & Tucker-Drob, [20], safe attachments (Belsky, Houts & Fearon, 2010) and regulation of self Moffitt, Arseneault & Caspi, [21]. Gender has been identified as one of the major correlates of sexual initiation Asante, Nketiah-Amponsah, Andor-Arthur, Boafor & Amponsah, [22] and is one of the factors responsible for the high prevalence of HIV among young people Matson, Beguy & Kabiru, [23] since those that debut sexual activity at a very young age are more likely to have several sexual partners at the same time, engage in commercial sex and consequently catch HIV, among other STDs Matson, Beguy & Kabiru, [23]; Onsomu, Duren-Winfield & Harwell, [24]. Early sex debut impacts on school outcomes and a rise in unintended pregnancies Peltzer, [25].…”
Section: Introductionmentioning
confidence: 99%